Demplot "Downstream TFD-Bakar Batu Based On Hydroganic Rotating Tunnel Innovation" Towards Green Economy and Millennial Tourism in the Digital Society Era" - Pither Boimau; Bani Aplonia; Grasia Dwi Handayani (Journal of Social Research, 2023)
This research was conducted to carry out the technology transfer of "tunnel fish dryer-burnt stone" (TFD-Bakar Batu) as a drying device to support production results from millennial tourism "tunnel hydrogenic rotating," which did not sell out in one production cycle. The method was used through direct interviews and online questionnaire assistance for millennials, with a total sample of 13,871 respondents and farmers, with a total sample of 30: furthermore, the method for measuring the temperature at THR for environmental impacts. Testing the first hypothesis about the motivation level of farmers and millennials for the TFD-Bakar Batu and THR demonstration plots uses a proportional test with the following hypotheses: Ho : P < 50% Ha : P > 50% Description: Ho: Although allegedly less than or equal to 50% of millennials are interested in the THR and H1 tourism demonstration plots, it is suspected that more than 50% of the farmers have high motivation in implementing the THR tourism demonstration plot, which TFD-Bakar Batu supports—a statistical test using the Z count confirms this. From the results of the study, it was found that the number of millennials who were interested was 8,514 (61.37%), and those who were not interested were 5,357 (38.63%); motivated farmers were as many as 28 (93.3%), and those who did not be motivated were as many as two (6.7%).